Performance evaluation in vanet by using virtual carrier sense with packet size variation - Verma, Sahil; Mittal, Sonu (International Journal of Engineering and Technology, 2018)
Late investigations exhibit that the directing convention exhibitions in vehicular systems can enhance utilizing dynamic data on the movement conditions. WSNs (Wireless Sensor Networks) and VANETs (Vehicular Ad Hoc Networks) are precisely related with this announcement and speak to the pattern of remote systems explore program in the most recent years. In this unique situation, another kind of system has been produced: truth be told, HSVN (Hybrid Sensor and Vehicular Network) let WSNs and VANETs coordinate through powerful data information trades with the intend to enhance street security, and particularly to caution the driver and the co-pilot of any occasion happened in the street ahead, for example, congested road, mishaps or terrible climate. The outcomes will be prompt: less mischances implies more spared lives, less activity implies a contamination diminish, and from the mechanical perspective, this correspondence convention will open the way to appealing administrations, for example, downloading of interactive media administrations or web perusing, that implies less demanding, more secure and more agreeable excursionsÂ